Dietary Hydroxyproline + Vitamin C and Eucommia ulmoides Improved the Growth and Flesh Quality of Pacific White Shrimp (Litopenaeus vannamei) - Xinyi Fei; Xiaoqin Li; Tianyu Huang; Beiping Tan; Xiangjun Leng (Animals)
Pacific white shrimp (Litopenaeus vannamei) is an important aquaculture shrimp in China and globally due to its high nutritional value and delicious flavors [...]